The Language Features of the Coronation of "Pohutu Momulanga" in Forming the Leadership Identity of the Gorontalo Community - Haris Danial; Muhammad Rayyan Kufri; Ayu Hidayati Ali; Sri Rumiyatiningsih Luwiti; Kessy Pramesti Mokodompit (JIMAD : Jurnal Ilmiah Mutiara Pendidikan, 2023)
The use of language in society is not only limited to reflecting local wisdom, but the language features contained  are able to build human character. The aim of this research is to describe the features of the Pohutu Momulanga language in forming the leadership identity of the Gorontalo people. Data was collected using paradox observer techniques and observation techniques. Research data was analyzed using pragmatic aspects by Leech (1983). The results of the research show that there are 5 (five) language features in Pohutu Momulanga's coronation ceremony, including: standard, literary, parable, rhyme, and archaic. Meanwhile, 5 (five) speech acts were found that were reflected in tuja'I, including: respecting, informing, promising, giving a message, and announcing.